Chapter 3 Defining Difference Competing Forms of Ovarian Surgery in the Nineteenth Century - Frampton, Sally (Rochester Studies in Medical History, 2017)
Ovariotomy provides a useful way of unpacking not just the process of surgical innovation but also the usefulness of innovation as an analytical category in the history of medicine. How might we pin down the meaning of "innovation"-let alone "alternative innovation"-in surgery when these innovations themselves are unstable, changing entities that are difficult to define? Through the example of ovariotomy I show that alternative innovation need not necessarily imply competition between diverse innovations, but that such a framework might also be used to consider how different versions of the "same" operation arise.